SAT0535 CLINICAL COURSE IN PATIENTS WITH INTERSTITIAL PNEUMONIA WITH AUTOIMMUNE FEATURES (IPAF) IN A MULTIDISCIPLINARY CONSULTATION. (2nd June 2020) - Perez, I.; Vadillo, C.; Nieto, M. A.; Freites, D.; Rosales, Z.; Mucientes, A.; León, L.; Font, J.; Jover, J. A.; Abasolo, L.
Abstract : Background: A proportion of patients with Interstitial Lung Disease (ILD) show autoimmune characteristics but do not completely meet the classification criteria for a definitive connective tissue disease. In order to unify the nomenclature and criteria to define this condition, the classification of patients with Interstitial Pneumonia with Autoimmune Features (IPAF) has recently been adopted (Fisher, et al). Objectives: To describe the sociodemographic, clinical, functional characteristics and therapeutic management of IPAF patients in clinical practice and to evaluate the incidence rate of functional respiratory impairment over time. Methods: A longitudinal observational study was performed. Patients with IPAF classification criteria (Fischer et al) were included from the time of ILD diagnosis (Feb 2017 to Sept 2018) and followed until loss of follow-up or end of the study (Oct 2019), in a multidisciplinary team, carried by a pneumologist and a rheumatologist in a Tertiary Hospital in Madrid. Main outcome: relative functional respiratory impairment: defined as decline in percent predicted forced vital capacity (FVC%) of ≥ 5% compared to the previous visit. Respiratory function was measured at baseline and every 6 months. Covariates: a) sociodemographic, b) clinical, c) radiological pattern (non-specific interstitial pneumonia [NSIP]; usual interstitial pneumonia [UIP], others); d) FVC%, DLCO%; e) laboratory tests; f) therapy used (glucorticosteroids, disease modifying antirheumatic drugs (DMARDs) and Biologic Agents). Statistical analysis: description of the sociodemographic, clinical, radiological, functional and treatment characteristics of the patients. Survival techniques were used to estimate the incidence rate (IR) of relative functional respiratory impairment, expressed per 100 patient-semester with their respective confidence interval [95 % CI]. Results: 17 patients were included with a mean follow-up of 3 ± 1.5 years, 70.6% were women with a mean age of 65±10 years. The most frequent IPAF classification criteria were: a) clinical: arthritis (50%), Raynaud`s phenomenon (33%) and mechanical hands (17%); b) serological: 65% had ANA ≥1/360; 31% FR> 40; 30% Anti-Ro positive; c) morphologic: 59% presented NSIP pattern and 29.4% was UIP. The baseline median FVC% and DLCO% were 89 [83-107.7] and 63 [50-79.8] respectively. During the study period, 94% received treatment: 87.5% glucorticosteroids, 68.5% mycophenolate, 56% azathioprine, 18.7% cyclophosphamide iv and 33% antifibrotics. During the follow-up (104.6 patient - semester), 15 patients presented relative functional respiratory impairment, with an IR of 23.8 [16.1-35.3]. After 14 months from IPAF diagnosis 50% of the patients had relative functional respiratory impairment. At the end of the follow-up, 50% showed a worsening of the DLCO%. Conclusion: IPAF patients are mostly women in their sixties. The most frequent clinical criteria are arthritis and Raynaud`s phenomenon and the serological were FR and ANAs. The most frequent radiological pattern was NSIP. The therapeutic management is mainly with glucorticosteroids, mycophenolate and azathioprine. At the beginning, patients have a slightly diminished lung function. These patients have significant functional impairment over time that will impact in their prognosis. Longitudinal and multicenter studies are necessary to advance in the knowledge and management of these patients. References: [1]Fischer A, Antoniou KM, Brown KK, Cadranel J, Corte TJ, du Bois RM, et al. An official European Respiratory Society/American Thoracic Society research statement: interstitial pneumonia with autoimmune features. Eur Respir J [Internet]. 2015 Oct;46(4):976–87. Available from: http://www.ncbi.nlm.nih.gov/pubmed/26160873 Disclosure of Interests: None declared